Effect of non‐surgical weight management on weight and glycaemic control in people with type 2 diabetes: A comparison of interventional and non‐interventional outcomes at 3 years. Issue 4 (11th January 2018) - Botha, Shani; Forde, Lorna; MacNaughton, Sheila; Shearer, Ross; Lindsay, Robert; Sattar, Naveed; Morrison, David; Welsh, Paul; Logue, Jennifer
Abstract : Aims: To examine the long‐term effectiveness of lifestyle weight management interventions, recommended in clinical guidelines for patients with type 2 diabetes mellitus (T2DM) and obesity. Materials and methods: Electronic health records were used to follow 23 208 patients with T2DM and obesity in Glasgow, UK, for up to 3 years between 2005 and 2014. Patients were stratified by referral to and attendance at a lifestyle weight management intervention, and by attainment of a target weight loss of ≥5 kg over 7 to 9 sessions ("successful completers"). Outcomes were change in weight, glycated haemoglobin (HbA1c) and diabetes medications. Results: A total of 3471 potentially eligible patients were referred to the service, and fewer than half of these attended ( n  = 1537). Of those who attended 7 to 9 sessions, >40% successfully completed and achieved 5‐kg weight loss (334/808). Successful completers maintained greater weight loss (change at 3 years −8.03 kg; 95% confidence interval [CI] −9.44 to −6.62) than the non‐completers (−3.26 kg; 95% CI −4.01 to −2.51; P  < .001) and those not referred to the service (−1.00 kg; 95% CI −1.15 to −0.85; P  < .001). Successful completers were the only patient group who did not increase their use of diabetes medication and insulin over 3 years. In adjusted models, successful completers had a clinically significant reduction in HbA1c (−3.7 mmol/mol; 95% CI −5.82 to −1.51) after 3 years; P  ≤ .001) compared with non‐completers and unsuccessful completers. Conclusions: A real‐life structured weight management intervention in patients with diabetes can reduce weight in the medium term, result in improved glycaemic control with fewer medications, and may be more effective than pharmacological alternatives. Challenges include getting a higher proportion of patients referred to and engaged with interventions.